Analysis of single PEM fuel cell performances based on current density distribution measurement - Ghosh, P. C.; Wuester, T.; Dohle, H.; Kimiaie, N.; Mergel, J.; Stolten, D. (Journal of Fuel Cell Science and Technology, 2006)
A new in situ measurement method of mapping the current density distribution in polymer electrolyte fuel cells (PEFC) is used to analyze the performance of a fuel cell under different operating conditions. The present method is useful in investigating the current density distribution in a single cell as well as a stack, which carries the information about the local reactant activity over the electrode area It was found that the current density close to the gas inlets is strongly influenced by the reactants' relative humidity. The performance close to the gas outlets is greatly influenced by the inlet gas pressures and the stoichiometry factors of the reactant gases, mainly on the cathode side. It was also observed that the performance of the fuel cell drops with the increase in operating temperature if the reactant gases are not sufficiently humidified.
Keywords: current density distribution; fuel cell performance; PEFC

DMFC at low air flow operation: study of parasitic hydrogen generation - Dohle, H.; Mergel, J.; Ghosh, P. C. (Electrochimica Acta, 2007)
In this paper, the effect of hydrogen generation in direct methanol fuel cells (DMFC) is described. Under certain operating conditions hydrogen generation occurs in DMFC causing an additional methanol consumption and a decrease of the cell voltage. For the present experiments a segmented cell with an active area of 244 cm 2 is used. The cell has 196 segments which are regularly distributed on the whole area. By this experimental setup hydrogen generation was found in regions with insufficient air supply. Hydrogen generation was analyzed by systematically applying different air flow rates and detecting the local current densities. The theory for hydrogen generation is confirmed by the results obtained from the segmented cell. A correlation between open circuit voltage (OCV), air flow rate and hydrogen generation was observed. Furthermore, half-cell measurements with different methanol concentrations were performed and used for analyzing the processes during hydrogen generation. The work clearly indicates the importance of sufficient cathode air supply for DMFC. Starved cathode areas not only do not contribute to the overall current generation but in addition reduce the power and efficiency by the parasitic generation of hydrogen. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: DMFC; Efficiency; electrolytic hydrogen evolution; oxygen depletion; side-effects